Prognostic value of non‐resistant and resistant masked uncontrolled hypertension detected by ambulatory blood pressure monitoring. Issue 5 (17th March 2022) - Coccina, Francesca; Pierdomenico, Anna M.; Cuccurullo, Chiara; Pizzicannella, Jacopo; Guagnano, Maria T.; Renda, Giulia; Trubiani, Oriana; Cipollone, Francesco; Pierdomenico, Sante D.
Abstract: Masked uncontrolled hypertension (MUCH) is at higher cardiovascular risk than controlled hypertension (CH). In previous studies, patients with MUCH were considered as a unique group though those receiving ≤2 drugs could be defined as having nonresistant MUCH (NRMUCH) and those receiving ≥3 drugs as having resistant MUCH (RMUCH). The aim of this study was to assess the prognostic value of NRMUCH and RMUCH detected by ambulatory blood pressure (BP) monitoring. Cardiovascular risk was evaluated in 738 treated hypertensive patients with normal clinic BP. Patients were classified as having CH or MUCH if daytime BP < or ≥ 135/85 mmHg, respectively, regardless of nighttime BP, or CH or MUCH if 24‐h BP < or ≥ 130/80 mmHg, respectively, regardless of daytime or nighttime BP. By daytime or 24‐h BP, the authors detected 523 (71%), 178 (24%), and 37 (5%) or 463 (63%), 231 (31%), and 44 (6%) patients with CH, NRMUCH, and RMUCH, respectively. During the follow‐up (median 10 years), 148 events occurred. After adjustment for covariates, compared to CH, the hazard ratio (HR), 95% confidence interval (CI), for cardiovascular events was 1.81, 1.27–2.57, and 2.99, 1.73–5.16, in NRMUCH and RMUCH defined by daytime BP, respectively, and 1.58, 1.12–2.23, and 2.21, 1.27–3.82, in NRMUCH and RMUCH defined by 24‐h BP, respectively. If RMUCH was compared with NRMUCH, the risk tended to be higher in RMUCH but did not attain statistical significance ( P  = .08 and P  = .23 by daytime and 24‐h BP thresholds, respectively). In conclusion, both NRMUCH and RMUCH are at increased cardiovascular risk than CH.